Asymmetric Effects of Human Rights on Renewable Energy Consumption - Irsan Hardi; Mustafa Necati Coban; Naftaly Mose; Suriani Suriani; M. Shabri Abd Majid (Leuser Journal of Environmental Studies, 2026)
As the transition to renewable energy has become increasingly important for achieving environmental sustainability, understanding the institutional factors that influence renewable energy consumption (REC) is crucial. This study examines the relationship between human rights and REC using a panel dataset covering five world regions (Africa, Asia, Europe, North America, and South America) from 1990 to 2024. Employing an asymmetric panel ARDL and the Dumitrescu–Hurlin panel causality test, the results reveal a significant long-run nonlinear relationship in which improvements in human rights increase REC, while deteriorations in human rights reduce REC. Short-run effects vary across regions, reflecting differences in institutional and developmental conditions. The causality analysis indicates a bidirectional relationship between human rights and renewable energy consumption. These findings suggest that strengthening human rights institutions can promote renewable energy adoption, support environmental sustainability, and facilitate the transition toward a cleaner energy system.